Class II and class III maternal obesity and pregnancy-related outcomes: a UK national study. (16th November 2010) - Fitzsimons, KJ; Modder, J
Abstract : Maternal obesity is now considered one of the most commonly occurring risk factors in obstetric practice. A UK-wide observational study was conducted to determine the prevalence of class II and class III maternal obesity and to assess the pregnancy-related outcomes in this high-risk group of women. Every maternity unit in the UK was requested to report each woman with a pregnancy body mass index (BMI) ≥35 kg/m 2 who gave birth during March and April 2009. Data relating to demographics, co-morbidities, anthropometric measures and pregnancy-related outcomes were collected. A total of 4751 women who had a calculated BMI ≥35 at any point during pregnancy were reported to have given birth during a 7-week period. The mean first-recorded antenatal weight was 104.9 kg and BMI 41.3 kg/m 2 . The majority (97.8%) of women gave birth in obstetric units, while 1.2% delivered in alongside-midwifery units, 0.3% in free-standing midwifery units and 0.6% at home. 46% of women had a spontaneous onset of labour, 33% were induced and 21% never laboured. Of the 4669 singleton deliveries, 55% were spontaneous vaginal births, 38% were Caesarean sections, 8% instrumental vaginal births and 0.2% vaginal breech births. Eight per cent of women undergoing Caesarean sections required general anaesthesia. Of the singleton babies, 1.3% had a confirmed congenital anomaly, 1% were stillborn and 0.2% had early neonatal deaths. Eight per cent of live born babies were admitted to the neonatal unit within 48 h of birth. Maternal obesity is associated with an increased risk of pregnancy-related complications and adverse outcomes.